Microbiological profile of frozen fruit pulps consumed in Brazilian northeast: A systematic review (Research, Society and Development, 2021)
The present study aimed to identify the microbiological profile of frozen fruit pulps consumed in Brazilian northeastern through a systematic literature review from studies published between 2016 and August 2021. The research was carried out in selected databases (Google Scholar, CAPES, and SciELO) using the following terms/descriptors: fruit pulp, microbiological profile, quality, northeast, and "fruit pulp", "microbiology profile", "quality", "northeast" in the combinations. The search results were selected and analyzed, understanding the study's objective, besides the inclusion and exclusion criteria. A total of 472 studies were found, with 20 articles being selected for data collection and synthesis. It was observed that most varied fruit pulps are consumed by the region, especially acerola, cajá, cashew, and passion fruit. The main microbiological parameters evaluated were: enumeration of total coliforms and thermotolerant coliforms (80%), mold and yeast count (70%), and Salmonella research (60%). The pulps of frozen fruits consumed in Brazilian northeastern present problems in the standardization of microbiological parameters established by the legislation, resulting in products improper for consumption. Given the stated, it stands out the importance of the correct application of good manufacturing practices and the training of the technical quality control as the inspection staff of the processing fruit pulps consumed in the northeast region of Brazil.